Evaluation of the Bond Strength, Durability, and Enamel Demineralization Potential of Orthodontic Adhesives on Bracket Bonding - Kamal Dhruvkumar Hotchandani; Anamika Anamika; Priya Manimegalan; Johar Rajvinder Singh; Harsh Pandey; Varunjeet Chaudhary (Journal of Pharmacy and Bioallied Sciences)
Objective: To evaluate the effects of incorporating titanium tetrafluoride (TiF4) into orthodontic primers on shear bond strength (SBS), bond durability, and enamel demineralization potential compared to conventional adhesive systems. Materials and Methods: In total, 120 extracted human premolars were divided into three groups (n = 40 each): Group A (Resin-based, Transbond XT), Group B (Glass ionomer-based, Fuji Ortho LC), and Group C (2 Wt.% TiF4-containing modified Transbond XT system). Standard edgewise premolar brackets were bonded to the teeth. Half of each group underwent immediate SBS testing, while the remaining specimens were thermocycled before testing. The Adhesive Remnant index was assessed post-debonding. Enamel demineralization was evaluated using quantitative light-induced fluorescence before bonding and after debonding. Results: Group C exhibited the highest mean SBS values both immediately (19.5 MPa) and after thermocycling (17.9 MPa). This group also showed the least enamel demineralization. Conclusions: The incorporation of 2 Wt.% TiF4 into the orthodontic primer resulted in improved bond strength and reduced enamel demineralization compared to conventional adhesive systems.